Assessing the appropriateness of Metformin prescribing in Diabetes type 2 patients, Inburi Hospital - Rattanapan, Piyawat (Journal of Medical and Public Health Region 4, 2023)
This retrospective descriptive study aimed to determine the appropriateness of metformin prescribing in diabetic type 2 patients and to study the incidence of metformin-associated lactic acidosis (MALA) in diabetic type 2 patients. This study was conducted by analyzing the data of patients diagnosed with diabetes type 2 (ICD10 disease code E11.0-E11.9) who were treated at Inburi hospital Between October 1, 2021 and September 30, 2022. A total of 2,596 diabetes patients with 10,580 visits were included. Metformin was appropriately prescribed in 96.12% of follow-ups (n=10,169). The incidence of acute renal failure was 0.48% during the study (n=51). In addition, three patients with metformin-associated lactic acidosis (MALA) were found to have a serious adverse reaction with an incidence of 0.03% (n=3) (115.56 cases per 100,000 cases-years receiving metformin).All three patients developed acute kidney injury and one patient received renal replacement therapy. From this data, healthcare professionals should be aware of drug use rationally and guidelines for rational drug use should be established.